Isolation and characterization of a cDNA clone encoding avian skeletal muscle C-protein: an intracellular member of the immunoglobulin superfamily. - Einheber, S (1990)
C-protein is a thick filament-associated protein located in the crossbridge region of vertebrate striated muscle A bands. Its function is unknown. To improve our understanding of its primary structure, we undertook the molecular cloning of C-protein mRNA. We describe the isolation and characterization of a cDNA clone, lambda C-86, that encodes approximately 80% of the fast isoform of C-protein in the chicken. Sequence analysis of the insert revealed that C-protein, although an intracellular, nonmembrane-associated protein, is a member of the immunoglobulin superfamily. Like several cell surface adhesion molecules that belong to this superfamily, C-protein contains sequence motifs that resemble immunoglobulin domains and fibronectin type III repeats. Computer searches using the C-protein sequence also lead to the identification of related domains in chicken smooth muscle myosin light chain kinase that have not been reported previously.